1988
DOI: 10.7326/0003-4819-108-3-350
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim-Sulfamethoxazole for Acute Dysuria in Women: A Single-Dose or 10-Day Course

Abstract: Compared with single-dose treatment, 10-day treatment yields a superior cure rate at 2 weeks after the start of treatment, but by 6 weeks the advantage of longer treatment no longer exists. This effect may be explained by the lesser effectiveness of single-dose treatment in eradicating vaginal E. coli, resulting in more frequent same-strain recurrences within 2 weeks of treatment.(ABSTRACT TRUNCATED AT 400 WORDS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(22 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…Persistence of coliforms in the vagina after treatment has been found to be associated with frequent early recurrences of cystitis (5). We found in the current study, as we found in our previous study (9), that ofloxacin was initially more effective than trimethoprim-sulfamethoxazole in eradicating E. coli from the rectum, but colonization was high in all treatment groups several weeks after treatment.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Persistence of coliforms in the vagina after treatment has been found to be associated with frequent early recurrences of cystitis (5). We found in the current study, as we found in our previous study (9), that ofloxacin was initially more effective than trimethoprim-sulfamethoxazole in eradicating E. coli from the rectum, but colonization was high in all treatment groups several weeks after treatment.…”
Section: Resultssupporting
confidence: 76%
“…Previous studies of short-course treatment for uncomplicated cystitis in women have demonstrated an association between posttreatment recurrence of UTI and a previous history of UTI (5,18), high-quantity bacteriuria (5), and diaphragm use (5). Likewise, in our study, a history of UTI in the previous year and diaphragm use were associated with persistent or recurrent significant bacteriuria in each study group.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The high in vitro resistance to ampicillin and sulfonamide and the high cost of amoxicillin/clavulanate and the cephalocrystalline sporins limit their usefulness in the setting of acute uncomplicated cystitis. More than 90% of females report the absence of acute urinary symptoms within 72 hours after commencement of antimicrobial therapy (Fihn et al 1988). Phenazopyridine or Uristat can be prescribed in females with severe persistent dysuria.…”
Section: Managementmentioning
confidence: 99%
“…More recently, trimethoprim was found to act as an inhibitor of bacterial dihydrofolate reductase (5). The combined application of trimethoprim and a sulfonamide is an important protocol for the treatment of bacterial infections (5)(6)(7)(8).…”
mentioning
confidence: 99%